2001
DOI: 10.1038/sj.ejhg.5200613
|View full text |Cite|
|
Sign up to set email alerts
|

Parental mosaicism of JAG1 mutations in families with Alagille syndrome

Abstract: The Alagille syndrome (AGS), a congenital disorder affecting liver, heart, skeleton and eye in association with a typical face, is an autosomal dominant disease with nearly complete penetrance and variable expression. AGS is caused by mutations in the developmentally important JAG1 gene. In our mutation screening, where 61 mutations in JAG1 were detected, we identified five cases where mosaicism is present. Our results point to a significant frequency of mosaicism for JAG1 mutations in AGS of more than 8.2%. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 19 publications
(8 reference statements)
0
39
0
Order By: Relevance
“…44 The occasional finding of a cytogenetically visible deletion or rearrangement involving 20p12 was significant in allocating the ALGS locus to this region, 9,45 and the similarity of the phenotype between deletion and mutation cases suggests that haploinsufficiency is the mutational mechanism. Approximately 60% of mutations are de novo, and germline mosaicism may occur at a frequency up to 8%, 46 which must not be overlooked in genetic counselling, where appropriate.…”
Section: Pathogenesismentioning
confidence: 99%
“…44 The occasional finding of a cytogenetically visible deletion or rearrangement involving 20p12 was significant in allocating the ALGS locus to this region, 9,45 and the similarity of the phenotype between deletion and mutation cases suggests that haploinsufficiency is the mutational mechanism. Approximately 60% of mutations are de novo, and germline mosaicism may occur at a frequency up to 8%, 46 which must not be overlooked in genetic counselling, where appropriate.…”
Section: Pathogenesismentioning
confidence: 99%
“…7 **When screening parents for their child's known mutation, it is important to note that a negative result does not rule out the possibility of germline mosaicism. 12 2.2 Analytical specificity (proportion of negative tests if the genotype is not present) Analytical specificity is nearly 100%. False positives are rare.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…While mosaicism for alterations in Jagged1 may account for some of the clinical variability seen in this disorder, it is a rarely reported finding. The case presented by LauferCahana et al is the only mosaic 20p12 deletion reported, while other evidence indicates that some individuals may be mosaic for point mutations as well [Giannakudis et al, 2001]. Mosaicism would be an unlikely mechanism for variable expression in large multigeneration families, and the possibility of other genes modifying the severity of the symptoms has been suggested.…”
mentioning
confidence: 91%